The use of quantitative ultrasound to investigate bone strength in the facial skeleton - (:unkn) unknown (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2018)
Study background Osteoporosis is the most common metabolic bone disease in the world, and is one of the leading causes of fragility fractures in elderly people, resulting in a number of comorbidities and loss of mobility. It is diagnosed by the use of Dual Energy X-Ray Absorptiometry (DXA), which is considered the gold standard in fragility fracture risk prediction. DXA scan provides a result based on bone mineral density (BMD). Quantitative ultrasound (QUS) is another method for detecting osteoporosis, which utilises propagation of an ultrasound wave through the tissue, providing a measurement based on signal attenuation and speed. Quantitative ultrasound of the calcaneus (heel bone) has been shown in a number of studies to have a similar ability to DXA scan to diagnose osteoporosis. More recently, multisite QUS (mQUS) has been developed for use on multiple peripheral sites throughout the body, including the metatarsal, radius, phalanx, and tibia. This device (Omnisense 8000, BeamMed, Israel) generates a Speed of Sound (SOS) reading, which correlates to bone strength. A recently published study has shown that the use of multisite QUS on the mandible can differentiate between osteoporosis sufferers, and healthy individuals. This study aims to investigate whether there are other facial sites that show this change, and determine if facial bone QUS can detect change in response to osteoporosis treatment. Materials and methods Two groups of subjects were recruited for this study: healthy premenopausal women, and women with DXA confirmed osteoporosis. Subjects were excluded from the control group if they had any significant risk factors for osteoporosis or a history of fracture not due to a high impact trauma. SOS readings were taken from the parasymphysis of the mandible, the frontal bone, and the zygomatic arch. To compare results to already mQUS established sites. Readings were also taken from the radius and the metatarsal. Readings in the osteoporotic group who were undergoing treatment were repeated after one year to determine if there was a response to treatment. Where available, the results were compared to DXA scans, bone biomarkers, and calcaneal ultrasound. Results A total of 170 subjects were enrolled in this study: 84 control subjects and 86 osteoporotic subjects. Mean SOS readings for the mandible were found to be 3,504 (SD 221) ms-1 for the control group and 3,298 (SD 239) ms-1 for the osteoporotic group. This difference was found to be statistically significant after controlling for the effect of age, height, weight, and number of missing teeth (p<0.001). No other significant differences were found between the other two facial sites. The zygomatic arch was found to be an unreliable site to successfully obtain readings. Difficulty in obtaining zygomatic arch readings was found to be significantly related to age (rpb =- 0.296, p<0.0001). No significant differences were found at any of the five measured sites in the osteoporotic group between SOS readings taken at recruitment and those taken at after one year. Conclusions This study has shown that there are changes in the mandible as a result of osteoporosis. Such changes are detectable by the use of multisite axial quantitative ultrasound device, and this may be utilised routinely in the future as part of a patient work up in a bone health clinic. The results from the zygomatic arch are inconclusive due to a high number of failures to obtain readings. However, the difficulty in obtaining readings increased significantly with age suggesting that there are morphological changes in the zygomatic arch related to age. No response to treatment was seen with SOS readings at any of the measured five sites over a one- year treatment course. However, of the subjects recruited who had a DXA scan at baseline and the one year mark, no BMD response to treatment was detected either. Out of the five sites investigated in this study, the mandible demonstrated the strongest correlation between changes in SOS and changes in BMD over the observation period. This finding is significant considering that the radius and the metatarsal are two sites already established for use with mQUS, with a reasonable volume of evidence.
APPROVED